2018
DOI: 10.2134/agronj2017.04.0222
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sunflower to Nitrogen and Phosphorus in North Dakota

Abstract: Core Ideas Nitrogen availability and fertilization can increase sunflower see yield.Nitrogen fertilization may decrease oil concentration of oilseed sunflower.Nitrogen fertilization increases sunflower lodging risk in windy regions. The N and P recommendations for sunflowers growers in North Dakota have not been changed in 30 yr. Twenty‐two N and P rate experiments were conducted during 2014 and 2015. The objective was to determine the response of seed yield, oil concentration, and lodging to available N and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 26 publications
6
39
5
Order By: Relevance
“…The amount of work required increased by the need to develop recommendations for multiple regions that consider the effects of different soil types, climates, crop growth habits, and crop requirements. Several studies documented that soil type variation could have a significant impact on P response towards crop yield [29][30][31][32][33], as demonstrated in the introduction. A study at University of Kentucky on P showed the differences that occurred from testing soil P (Mehlich III solution) using different soils with the same rate of P application [33].…”
Section: Sufficient Soil P and Soil Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of work required increased by the need to develop recommendations for multiple regions that consider the effects of different soil types, climates, crop growth habits, and crop requirements. Several studies documented that soil type variation could have a significant impact on P response towards crop yield [29][30][31][32][33], as demonstrated in the introduction. A study at University of Kentucky on P showed the differences that occurred from testing soil P (Mehlich III solution) using different soils with the same rate of P application [33].…”
Section: Sufficient Soil P and Soil Variabilitymentioning
confidence: 99%
“…Several studies documented that soil type variation could have a significant impact on P response towards crop yield [29][30][31][32][33], as demonstrated in the introduction. A study at University of Kentucky on P showed the differences that occurred from testing soil P (Mehlich III solution) using different soils with the same rate of P application [33]. Therefore, it was necessary to study the soil types in Maine and Aroostook County, Maine.…”
Section: Sufficient Soil P and Soil Variabilitymentioning
confidence: 99%
“…However, these treatments were not significantly different from the control. Schultz et al (2018) also found that sunflower yield increased with N rate until reaching the critical level and the required N rate to maximize the yield at the conventional tillage site of eastern North Dakota was 200 lb N/ac. For this study, total soil available N (initial soil N + fertilizer N) for the 100% of recommended fertilizer N treatment was close to 190 lb N/ac.…”
Section: Seed Yield and Soil Inorganic Nmentioning
confidence: 85%
“…Current fertilizer N recommendation for eastern conventional till oilseed sunflower N recommendation ranges between 47 and 150 lb N/ac based on the cost of fertilizer N and sunflower price (Franzen, 2016). Recently, Schultz et al (2018) reported that 14 out of 21 sites responded to fertilizer N additions with the yield response curve in response to incremental fertilizer N application rates following a quadratic relationship in North Dakota and South Dakota.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these traits suggest nutrient uptake, and/or allometric scaling of root traits with vigor (Wang et al, 2019), as key components in vegetative growth. In a field setting, increased fertilization indeed produces increased growth in sunflower, though this did not ultimately translate into a yield increase; instead, it resulted in increased lodging and reduced yields (Schultz et al, 2018). This finding highlights the complexity of translating vegetative growth to yield.…”
Section: Discussionmentioning
confidence: 99%